A Cashless Policy and Economic Development in Nigeria - Fatogun Olukunle Ibukun; Ajao Chukwudumebi Cynthia (Randwick International of Social Science Journal, 2020)
A cashless economy is an environment in which money is spent without being physically carried from one place to another. It is meant to be an economic setting where services and goods are paid for via electronic which includes credit cards, bank transfer and Cheques, with no bill or money handed from one person to another. The cashless policy was introduced in January 2012, the robust interest which the policy has generated is surprising considering the effects on the business environment and particularly lives of ordinary Nigerians. The study showed that cashless policy reduces the movement of cash through usage of ATM, fund transfer, mobile banking. It helps financial transactions to be done without delay, it reduces money laundering. The study indicated that there is a very weak positive relationship between cash movement, joint effect of delivery of financial transactions and cashless policy (R= 0.245) and the model is not significant. However, for the relationship between internet availability, cashless policy and cash movement, the relationship between cash movement, the joint effect of internet availability and cashless policy is also weak ( R = 0.295 ). The model is also significant. The policy is faced with challenges ranging from erratic power supply, electronic fraud, lack of adequate sensitization, poor internet services, high rate of illiteracy and computerization. The benefits include but not limited to reduction in revenue leakages, it helps to reduce cash related crimes, the cost of handling cash is reduced to the barest minimum